Supramaximal interval training using anaerobic speed reserve or sprint interval training in rowers - Tongwu, Y.; Jinghui, Z.; Chuanwei, D.; Zijian, Z.; Yuxiong, X. (Frontiers in Physiology, 2025)
Objective: This study aimed to compare the consistency of physiological adaptations and inter-individual variability in response to three distinct high-intensity interval training (HIIT) protocols—anaerobic power reserve (APR), maximal aerobic power (MAP), and sprint interval training (SIT)—among elite male rowers. By exploring the impact of individualized intensity prescriptions, we sought to identify the most effective protocol for enhancing training consistency, as well as improving both aerobic and anaerobic performance while minimizing variability in individual responses.